Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s40337-020-00288-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of women with high vs. low food addiction tendency: a pilot study with voxel-based morphometry

Abstract: Background: The concept of 'food addiction' (FA) posits that highly processed food with added fat and/or refined carbohydrates is capable of triggering addictive-like eating behavior. FA may be one possible phenotype in obesity. Methods: The present voxel-based morphometry (VBM) study compared data from three groups of women. One group scored high on the Yale Food Addiction Scale (YFAS) and was overweight (n = 21), whereas the two other groups had low YFAS scores and were either overweight (n = 21) or normal-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The involvement of the left DLPFC has been previously described in overeating as a key region for inhibitory control processes [ 42 ]; for instance, low levels of activation in the left DLPFC have been linked to impaired goal-oriented behavior and uncontrolled eating in obesity [ 23 ]. Whereas, the MFG regional volumes have been associated to disinhibition toward food in normal and over-weight adults [ 14 ] and with increased BMI after one year in young females, suggesting a role of this region in weight gain [ 43 ]. The reason for our results showing greater GMV in this region, however, deserves further exploration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The involvement of the left DLPFC has been previously described in overeating as a key region for inhibitory control processes [ 42 ]; for instance, low levels of activation in the left DLPFC have been linked to impaired goal-oriented behavior and uncontrolled eating in obesity [ 23 ]. Whereas, the MFG regional volumes have been associated to disinhibition toward food in normal and over-weight adults [ 14 ] and with increased BMI after one year in young females, suggesting a role of this region in weight gain [ 43 ]. The reason for our results showing greater GMV in this region, however, deserves further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Along with fMRI evidence, recent structural MRI studies supported a significant connection between eating behavior, weight condition and brain cortex morphometry in prefrontal regions [ 10 , 11 , 12 ]. Reduced gray matter volume (GMV) in the left prefrontal regions (including the dorsolateral PFC, DLPFC and Inferior Frontal Gyrus, IFG) was reported in individuals with obesity [ 13 ] and overweight women with food addiction (i.e, an addictive-like eating of highly processed food) [ 14 ]. Consistently, GMV in the middle frontal gyrus (MFG) has been found to be negatively correlated with disinhibition toward food and positively correlated with hunger scores (i.e., the intensity of hunger sensations and the extent to which such sensations induce eating) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "reward control" signature refers to the extended reward network containing regions that generally influence/control the core reward system 16 . Compared to those with no food addiction, structural and resting-state neuroimaging studies in individuals with high BMI and food addiction showed lower grey matter volume and lower connectivity in the inferior frontal gyrus, a region involved in response inhibition and appetite control 17,18 . In addition, compared to healthy controls, patients with binge eating disorder and bulimia nervosa showed distinct morphometry in the reward regions, such as decreased grey matter volume in the dorsal striatum/caudate nucleus 19 .…”
mentioning
confidence: 91%